Kinetic Study on Removal of Phenol from Water by Organo-Bentonite - DIANATI TILAKI, RAMAZANALI; KARIMPOOR, SEDDIGHE (Asian Journal of Chemistry, 2010)
By a simple ion exchange process, Na+ in the bentonite structure can be replaced by cationic detergent molecules and produce organobentonite. By this process the surface properties of bentonite can be modified and the produced organo-bentonite can be used for removal of organic contaminants from water. In this study bentonite was treated with alkyldimethylbenzyl ammonium chloride (ADBAC). In sorption experiments, each batch test sample was prepared with 0.1, 0.5 and 1.0 g bentonite (B) and modified bentonite (MB) separately together with aqueous phenol solution. Adsorption of 10 and 50 mgL-1 phenol on to bentonite and modified bentonite were investigated separately. Batch kinetic and isotherm studies were carried out to evaluate the effect of contact time, initial concentration and pH. Removal of 10-100 mg L-1 phenol, by 10 gL-1 ordinary bentonite was 10-20 % whereas in the same condition removal by synthesized organo-bentonite, was 60-80 %. Adsorption was reached in equilibrium within 3 and 6 h for organo bentonite and bentonite, respectively. Adsorption kinetics obeys a first order reaction. Adsorption isotherms were fitted with Langmuir and Freundlich models. Corresponding constants of both models were calculated. Adsorption efficiencies were slightly increased with increasing the sorbents dose. Optimum pH for using synthesized sorbent was 7. The bentonite may function as a recyclable surfactant support for the adsorption and subsequent combustion of organic pollutants.